2007
DOI: 10.1111/j.1469-8749.2007.02009.x
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam in juvenile myoclonic epilepsy: long‐term efficacy in newly diagnosed adolescents

Abstract: The aim of this study was to evaluate the efficacy and tolerability of levetiracetam (LEV) monotherapy in juvenile myoclonic epilepsy (JME). The study group consisted of 32 patients with epilepsy (20 males, 12 females) with a mean age of 13 years 3 months (SD 7y 11mo) at seizure onset. LEV was administered as the first drug; all patients were followed up at 6 and 12 months. The dose that achieved seizure control ranged from 1000 to 2500mg/daily. At 6-month evaluation: 15 patients were seizure free; 14 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 21 publications
(43 reference statements)
1
28
0
2
Order By: Relevance
“…Most of the seizure types were found to be of tonic-clonic type. Preliminary evidence by Verrotti et al (2008) revealed that LEV may be effective for treating 32 adolescent patients with newly diagnosed Juvenile myoclonic epilepsy (JME). Verrotti and his colleagues found at 6-month evaluation: 15 patients were seizure free; 14 patients were responders (>50% reduction in seizures); and three patients had marginal effects (<50% reduction of seizures).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the seizure types were found to be of tonic-clonic type. Preliminary evidence by Verrotti et al (2008) revealed that LEV may be effective for treating 32 adolescent patients with newly diagnosed Juvenile myoclonic epilepsy (JME). Verrotti and his colleagues found at 6-month evaluation: 15 patients were seizure free; 14 patients were responders (>50% reduction in seizures); and three patients had marginal effects (<50% reduction of seizures).…”
Section: Discussionmentioning
confidence: 99%
“…[46] In 32 patients with epilepsy (20 males, 12 females) with a mean age of 13 years 3 months (SD 7 years 11 months) at seizure onset, levetiracetam was administered as the first drug. The dosage that achieved seizure control ranged from 1000 to 2500 mg day.…”
Section: Juvenile Myoclonic Epilepsymentioning
confidence: 99%
“…Ethosuximide can be added to control absence seizures, if these are prominent. Levetiracetam has shown efficacy in open-label and randomized, double-blind, placebo-controlled trials against GTCS and myoclonic seizures in different types of idiopathic generalized epilepsies [34,[84][85][86][87][88]. In our centre, this is the first-line medication now, given its better sideeffect profile than valproate and topiramate, and its clearly greater efficacy compared with lamotrigine.…”
Section: Juvenile Myoclonic Epilepsymentioning
confidence: 99%